(untitled) (International Seven Journal of Health Research, 2024)
Colorectal neoplasms are among the most common types of neoplasms in the global population. Traditionally, they affect the older population. However, in recent years, younger and younger populations are being diagnosed with this comorbidity. This is due to various factors, such as the development and improvement of screening and diagnostic methods, as well as changing lifestyles among younger people. This has naturally led to the need to develop and improve treatment techniques. This literature review seeks to bring together the main findings of recent years, from screening to treatment of colorectal neoplasms.